A sutil diagnose morfológica entre as espécies simpátricas Stegastes fuscus E S. variabilis (ACTINOPETRYGII: POMACENTRIDAE) - Araújo, Maria Elisabeth de (2003)
The species of genus Stegastes are very difficult to identify. To minimize this problem 34 individuals of S. fuscus and 28 of S. variabilis collected at Tamandaré (PE) reef area were examined and a bibliographical comparative study of the Stegastes species occurring in Brazil were carried out to assess the diagnosis characters. The existing identification keys consider as the main diagnosis characters of coloration, the scales rows disposed in the face and the principal scales rows on the operculum. The color utilization to identify species is a problem because the individuals in fish collections are preserved in formaldehyde and utterly lose their color pattern. Besides, the Stegastes species present sexual and ontogenetic color change, with the younger stages showing more specific and contrasting color, while most adults are more uniform in brown tones, causing identification confusion even on live individuals. The body shape and proportions of most species are similar and throw doubts on the use of the morphometric characters to identify species. The meristic characters are more reliable but there is an overlap of the scales and rays counting interval. Many difficulties were found in the present study in the use of this genus identification keys, being extremely necessary a taxonomic revision of the existing species, before new species description. It is necessary to include new biochemical or molecular identification techniques to determine the presence of genetic flux between sympatric species, including the possibility of hybridization process. Key words: Stegastes, diagnosis, polymorphism, Brazil